1993
DOI: 10.1080/00140139308967868
|View full text |Cite
|
Sign up to set email alerts
|

Gender, ageing, and shiftwork intolerance

Abstract: The study investigated the hypothetical differences between male and female shiftworkers in their susceptibility to shiftwork-related health and social problems, with the special reference to the role of the age factor. The comparison concerned two matched-for-age-and-occupation groups of men and women, each of 83 persons, selected from the larger studied population of more than 700 workers in a Polish steel plant. The subjects were crane-operators employed in the same forward-rotated, three-shift, four-team s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 1 publication
5
41
0
4
Order By: Relevance
“…Additionally, we currently report that the amplitude of the variation was significantly increased in women vs. men due to a larger decline of alertness scores at night. This observation may partially explain the lower tolerance to shift work (21), greater fatigue and sleepiness levels (22), and increased risk of work-related injuries (23) in female shift workers, although contradictory results have been reported (24) and other nonphysiological factors (e.g., marital and parental status, socioeconomic factors) could be involved. Current results indicate lower values of alertness in the night and in the early morning in women, which is likely related to their higher prevalence of feeling unrefreshed upon awakening (19).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we currently report that the amplitude of the variation was significantly increased in women vs. men due to a larger decline of alertness scores at night. This observation may partially explain the lower tolerance to shift work (21), greater fatigue and sleepiness levels (22), and increased risk of work-related injuries (23) in female shift workers, although contradictory results have been reported (24) and other nonphysiological factors (e.g., marital and parental status, socioeconomic factors) could be involved. Current results indicate lower values of alertness in the night and in the early morning in women, which is likely related to their higher prevalence of feeling unrefreshed upon awakening (19).…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining crane operators working the same rotating shifts in a steel plant, women reported a shorter length of sleep, felt drowsier during their shifts, and were more likely to experience symptoms of chronic fatigue (27). Rotenberg (28) examined length of sleep among night shift workers during non-working days and found that women with children had shorter sleep lengths than men (16.8-33.3 hours versus 21.3-35.6 hours).…”
Section: Discussionmentioning
confidence: 99%
“…De fato, os estudos comparativos de homens e mulheres apresentam resultados contraditórios. Beermann e Nachreiner (1995), por exemplo, não observaram diferenças quanto aos aspectos da saúde subjetiva e a problemas psicossociais, ao passo que Oginska et al (1993) revelaram menor duração do sono e maior freqüência de queixas de sonolência entre trabalhadores do sexo feminino. Esses dados corroboram a observação de Dirkx (1991) quanto à comparação entre amostras femininas e masculinas.…”
Section: Determinantes Sociais E Estratégias De Cunho Social E/ou Domunclassified